POTENSI DAKWAH DI DAERAH MINORITAS DALAM PENGUATAN NILAI-NILAI AGAMA ISLAM - Kamaluddin Kamaluddin; Husna Sari Siregar; Lorisma Berutu (Studia Sosia Religia, 2022)
Tinada Village is one of the areas in Tinada District, Pakpak Bharat Regency, North Sumatra Province. Previously Pakpak Bharat Regency was part of Dairi Regency including Tinada Village and other villages that are still under the auspices of the present Pakpak Bharat Regency Government. The Pakpal Bharat area is predominantly Christian, so Islam is a minority population. The community in Tinada Village is a heterogeneous community, there are various clans that are characteristic of the Pakpak tribe and also various religions adhered to by the local community. With these characteristics, the Pakpak community can live side by side with other communities. This study aims to find out how the development of Islam in minority areas and how the potential/ability of Islamic da'wah in Minority Areas in Strengthening Islamic Values and what are the obstacles/constraints in developing Islamic da'wah in Tinada, Kec. Tinada, Kab. Mr. Bharat. This problem is studied through field research methods with a sociological approach. The formulation of the problem in this study is the development of Islamic da'wah in minority areas and the potential of Islamic da'wah in minority areas in strengthening Islamic values. The results of this study found that the development of Islam in the Tinada minority area is still relatively lacking in terms of empowerment. As well as the lack of awareness of some people who make Islam in Tinada difficult to realize Islamic values.